A history of Britain [videorecording] / : a complete collection - Schma, Simon (U.K : BBC, 2008)
NATIONS - covering the period 3100 BC to 1000 AD. Simon Schama starts his story in the Stone Age Village of Skara Brae, Orkney. Over the next four thousand years Romans, Anglo-Saxons, Vikings, Danes, and Christian missionaries arrive, fight, settle and leave their mark on what will become the nations of Britain. KING DEATH - covering 1348-1500. It took only six years for the plague to ravage the British Isles. Its impact was to last for generations. But from the ashes of this trauma an unexpected and unique class of Englishmen emerged. BURNING CONVICTIONS - covering 1500-1558. HEre SImon Schama charts the upheaval caused as a country renowned for its piety, whose king styled himself Defender of the Faith, turns into one of the most aggressive proponents of the new Protestant faith. THE BODY OF THE QUEEN - covering 1558-1603. This is the story of two queens: Elizabeth I , the consummate politician, and Mary Queen of Scots, the Catholic mother. It is also the story of the birth of a nation.
Disc 2
Keywords: Great Britain -- History; Great Britain -- Beginnings; Great Britain -- Conquest; Great Britain -- Dynasty